PENGARUH WHISTLEBLOWING SYSTEM DAN LITERASI TAX AUDIT TERHADAP TINDAKAN TAX EVASION (Studi Eksperimental pada Persepsi Mahasiswa Program Studi Akuntansi S-1 Universitas Pendidikan Indonesia) - Mahesa Dicky Taruna Supangat, - (2020)
This research examines specifically about tax evasion action based on tax audit literacy as an internal factor of tax payers and the whistleblowing system's condition as an control factor off the tax payers. Theory of Planned Behaviour can predict someone's action in comitting an act of cheating with three main construct, namely 1) control belief (whistleblowing system) able to encourage or hinder someone in making decisions, 2) attitude in deciding to do the tax evasion action, and 3) Subjective norms or the tax payers belief towards the Directorate General of Taxation in providing a good tax service and trust in managing taxes. The research method that used in this research is the experimental method with 2x2 factorial design. This research was conducted to undergraduate accounting studies of Indonesia University of Education that were selected using simple random sampling technique. Main hypothesis testing in this research uses Two Way ANAVA (Test for the main effect and for the interaction effect). The data that obtained is a tax evasion action in the form of amount of taxable income that will be reported (in percent), where as the result of the decision has previously received treatment of the condition of whistleblowing system and the existence of tax audit literacy. The result of this research in general indicate a decrease in tendency of someone will do the tax evasion. It can be achieved if the Directorate General of Taxation provide a good whistleblowing system as a control or the educational institusion provide learning about tax audit literacy to their students.